PERANCANGAN MEDIA PEMBELAJARAN HEAT TREATMENT BERBASIS ERGONOMIC FUNCTION DEPLOYMENT (EFD) di PT XYZ - Anis Nur Aini; Reza Ade Irmansyah; Waldoni Pramudita; Diki Taufik Hidayat; Kharida Rif’at Al Khumaidi; Achlis Haidar Rafi; Ferida Yuamita (KAMPUS AKADEMIK PUBLISING, 2026)
As a company engaged in fastener products, PT XYZ always prioritizes product quality. Through its training center, the company provides training for new employees, existing employees, and factory visitors who want to better understand the fastener product manufacturing process. Production machines, especially heat treatment machines, operate on a large scale, making it impossible to use them directly for basic training. The purpose of this study is to improve learning effectiveness by creating miniatures as an ergonomic learning medium for heat treatment. The EFD (Ergonomic Function Deployment) method is a user-centered design product development method that combines the principles of QFD (Quality Function Deployment) and ergonomics. Based on the results of the study, the highest priority scale was found in the attributes of miniatures that were able to represent heat treatment machines close to real conditions and display the sequence of processes in accordance with actual conditions. The success of the heat treatment learning media design was achieved by the achievement of the learning objectives, namely that users were able to understand the heat treatment process flow comprehensively and were able to operate the miniatures safely and easily.